The Effect of Active-Participant Experiments upon the Skills of Nursery Class Students to Recognize Measuring Instruments - Ozkan Sapsaglam; Aykut Emre Bozdogan (Journal of Education in Science, Environment and Health)
Preschool children learn through their senses. Children learn language, daily life skills, concepts and many other things through their senses. Thus, preschool educational environments and preschool educational activities should stimulate children’s senses. In this context, preschool science activities and experiments have positive effects upon children’s development and learning as they contain skills aimed at various senses like observation, relationship establishment, interpretation, inference and discussion. The objective of this study is to determine the effect of active-participant experiments upon the skills of preschool children to recognize and accurately select measuring instruments that are encountered in daily life and used in measuring various magnitudes. In the study, action research method was used. The study was conducted in the school year of 2015-2016 with totally 19 children (8 male and 11 female) aged 48-60 months. A total of 6 experiments (mass, weight, volume, length, temperature and time) were performed in 3 weeks to measure two magnitudes each week. In order to collect the study data, the researchers developed a measuring instrument of totally 6 questions, 3 of which were distracting. As a result of the study, it was determined that the experiments were effective upon the skills of children to recognize and accurately select measuring instruments that were used in measuring daily life magnitudes like mass, weight, volume, length, temperature and time.